A narrow endemic new species of Dendrobium sect. Stachyobium from Thailand (Orchidaceae: Malaxideae) - Prommanut, Phattaravee; Suddee, Somran; Kidyoo, Manit (Phytotaxa, 2018)
A new species belonging to Dendrobium section Stachyobium was discovered in mixed deciduous forest near the Check Point to Thi Lo Su Waterfall, Umphang District, Tak Province, in the northern Thailand. A description (including leaf anatomy), illustration and comparison with the closely related species D. incurvum are provided here.